2016
DOI: 10.1186/s13104-016-1874-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late sodium current inhibition on MRI measured diastolic dysfunction in aortic stenosis: a pilot study

Abstract: BackgroundRanolazine is a new anti-anginal drug that acts via late sodium current inhibition, and has been shown to improve diastolic dysfunction in isolated myocytes. Diastolic dysfuntion is common in patients with aortic stenosis (AS), and precedes symptom development and systolic dysfunction. The purpose of this study was to assess the effects of ranolazine on peak early diastolic strain rate (PEDSR) and exercise capacity in patients with AS.MethodsPatients with asymptomatic moderate to severe AS and diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To test whether ranolazine is equally effective in subjects with CMD who have no obstructive CAD, we leveraged the recently completed randomized, placebo‐controlled trial of late sodium current inhibition with ranolazine in CMD (NCT01342029) . In line with a recent study in subjects with aortic stenosis, we observed no major differences in diastolic or systolic function between the placebo arm and the ranolazine arm. Although the reason for this negative finding remains unclear, we acknowledge that it may be related to the treatment regimen.…”
Section: Discussionmentioning
confidence: 77%
“…To test whether ranolazine is equally effective in subjects with CMD who have no obstructive CAD, we leveraged the recently completed randomized, placebo‐controlled trial of late sodium current inhibition with ranolazine in CMD (NCT01342029) . In line with a recent study in subjects with aortic stenosis, we observed no major differences in diastolic or systolic function between the placebo arm and the ranolazine arm. Although the reason for this negative finding remains unclear, we acknowledge that it may be related to the treatment regimen.…”
Section: Discussionmentioning
confidence: 77%
“…The control groups were slightly younger than patient groups, but this was probably not a difference that could explain the effect seen ( Table 2 ) [ 29 , 32 ]. In patients with moderate-to-severe AS, the global diastolic peak circumferential strain rate closely resembled estimates for patients with DM2 and arterial hypertension ( Table 2 ) [ 30 ]. One study was found on inter-observer and inter-study reproducibility of global diastolic peak circumferential strain rate in patients with moderate-to-severe AS for both 1.5T and 3T [ 31 ]: the inter-observer variability was good for both 1.5T-CSAPMM (coefficient of variation 4%) and 3T-SPAMM (6%), but the inter-study reproducibility was only good-to-moderate for 1.5T-CSAPMM (coefficient of variation 19%) and poor for 3T-SPAMM (34%).…”
Section: Resultsmentioning
confidence: 74%